The E3 Ubiquitin Ligase Siah2 Contributes to Castration-Resistant Prostate Cancer by Regulation of Androgen Receptor Transcriptional Activity - Qi, Jianfei (2013)
Understanding the mechanism underlying the regulation of the androgen receptor (AR), a central player in the development of castration-resistant prostate cancer (CRPC), holds promise for overcoming the challenge of treating CRPC. We demonstrate that the ubiquitin ligase Siah2 targets a select pool of NCOR1-bound, transcriptionally-inactive AR for ubiquitin-dependent degradation, thereby promoting expression of select AR target genes implicated in lipid metabolism, cell motility, and proliferation. Siah2 is required for prostate cancer cell growth under androgen-deprivation conditions in vitro and in vivo, and Siah2 inhibition promotes prostate cancer regression upon castration. Notably, Siah2 expression is markedly increased in human CRPCs. Collectively, we find that selective regulation of AR transcriptional activity by the ubiquitin ligase Siah2 is important for CRPC development.